Self-Care Practice Among Individuals with Diabetes Attending Selected Hospitals in Kathmandu, Nepal - Karki, Lila; Rai, Lalita (Journal of Nursing Education of Nepal, 2024)
Introduction: Self-care is a cost-effective and essential practice that plays a vital role in preventing complications and enhancing the quality of life for individuals with diabetes. By improving self-care, it helps reduce the burden on healthcare systems and lowers overall healthcare costs. As self-care practices are highly individualized, this study aims to assess self-care behaviors among diabetic patients. Methods: A cross-sectional descriptive study was conducted among 205 adult clients with diabetics attending the outpatient departments at two public university hospitals located at Kathmandu . Data were collected through structured interviews using a five-point Likert scale. Descriptive and inferential statistics were used for analysis. The self-care was assessed in terms of diet, physical exercise, medication adherence and self-monitoring of blood glucose level. Results: In this study, nearly half (47.3%) of participants followed a calorie-counting diet, 64.4% ate meals on time, and 64.9% consumed dairy products. Over half of them regularly consumed cereals (53.2%) and green vegetables (52.7%). 76.1% ate lentils and 65.4% sometimes consumed beans. A majority of the respondents avoided high salt (68.3%), sugar (68.8%), and cold drinks (85.4%). Regarding physical activity, 66.8% engaged in 20–30 minutes of daily exercise; but, 83.9% did not perform brisk walking. Medication adherence was high, 99.5% taking prescribed doses and 92.6% did not change their medication without physician advice. Only 31.8% regularly monitored blood glucose, and 67.0% checked when needed without keeping records. Overall, 82.5% exhibited average self-care practices, with good medication adherence (92.7%) and an average dietary pattern (94.6%). A significant association was observed between age and self-care practices (p<0.028). Conclusion: This study shows high medication adherence but highlights gaps in diet, exercise, and blood glucose monitoring practices. Regular structured education program for diabetes people in these areas could improve overall diabetes self-care thus potentially enhancing outcomes.